35. THE SURGICAL OUTCOMES OF TREATING CRYPTORCHIDISM IN INFANTS AT THAI NGUYEN CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical characteristics, ultrasound imaging, and surgical outcomes of cryptorchidism in the inguinal canal in children at Thai Nguyen Central Hospital. Subjects andMethods: We conducted a study on 85 patients who underwent surgery, involving 102 testes descended to the scrotum, from January 2020 to March 2024 at the Pediatric Surgery Department of Thai Nguyen Central Hospital.Results: The average age of surgery was 3.64 ± 2.828 years, with the youngest being 1 and the oldest 12. The most common age group was 1- ≤5 years, accounting for 82.3%. Ultrasound detected 100% of the cases of undescended testes in the inguinal canal, with the most common location being in the inguinal canal (52.94%). All patients underwent open surgery to lower the undescended testes into the scrotum. The average surgery duration was 40.24 ± 6.326 minutes, and the average postoperative recovery time was 3.4353±1.051 days. Post-surgery, 82.4% of testes were positioned in the scrotum, while 17.6% were at the base of the penis. The TAI improved after surgery compared to pre-surgery levels.Conclusion: Surgery for undescended testes in the inguinal canal is safe and yields good treatment outcomes.
Keywords: Cryptorchidism; orchidopexy